2019
DOI: 10.1016/j.heares.2019.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Predicting individual speech intelligibility from the cortical tracking of acoustic- and phonetic-level speech representations

Abstract: Highlights: Objective EEG-based measure of speech intelligibility  Improved prediction of speech intelligibility by combining speech representations  Cortical tracking of speech in the delta EEG band monotonically increased with SNRs  Cortical responses in the theta EEG band best predicted the speech reception threshold Disclosure: The authors report no disclosures relevant to the manuscript.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
103
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 46 publications
15
103
2
Order By: Relevance
“…The second aim of this study involves how much each listening effort measure accounts for the unexplained variability in envelope tracking beyond speech understanding. Previous studies have shown that envelope tracking has the potential to be used as an objective measure of speech understanding (Vanthornhout et al, 2018;Decruy et al, 2019;Lesenfants et al, 2019;Verschueren et al, 2019). However, young NH participants show differences in neural envelope tracking that can not be fully attributed to changes in SNR or speech understanding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second aim of this study involves how much each listening effort measure accounts for the unexplained variability in envelope tracking beyond speech understanding. Previous studies have shown that envelope tracking has the potential to be used as an objective measure of speech understanding (Vanthornhout et al, 2018;Decruy et al, 2019;Lesenfants et al, 2019;Verschueren et al, 2019). However, young NH participants show differences in neural envelope tracking that can not be fully attributed to changes in SNR or speech understanding.…”
Section: Introductionmentioning
confidence: 99%
“…As these modulations, also called the speech envelope, are essential for speech understanding (Shannon et al, 1995), it has been suggested to measure neural tracking of the speech envelope to assess speech understanding. Recent studies have shown an increase in envelope tracking with increasing speech understanding supporting its potential as an objective measure of speech understanding (Ding & Simon, 2012;Vanthornhout et al, 2018;Decruy et al, 2019;Etard & Reichenbach, 2019;Lesenfants et al, 2019). Nevertheless, it is important to take into account that top-down processes can influence neural envelope tracking.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between the reconstructed/predicted artificial time-course and the actual values is then a measure of cortical speech tracking. Measures of cortical speech tracking quantify speech processing within the brain opening doors to, for example, an objective measure of an individual speech understanding [4][5][6][7] or auditory attention decoding in a cocktail party scenario [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…For the tracking of different speech features, the cortical activity in the delta (1 -4 Hz) and theta (4 -8 Hz) frequency bands has been found to be most important 4,5 . This could be partially explained by the matching of the time scale of such brain oscillations with the syllable (4 -8 Hz), word and phrase (1)(2)(3)(4) rates, suggesting a real-time transformation of the continuous acoustic information reaching the auditory cortex in those different linguistic representations [11][12][13][14][15] . On the contrary, the alpha and higher frequency bands show weak and noisy responses presumably reflecting the weaker phase locking of EEG neural data to the speech envelope at higher frequencies 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The correlations between the original neural responses and the predicted stimulus following responses are analyzed (Aiken and Picton, 2008;Di Liberto et al, 2015). The analysis of these correlations can not only contribute to advancing our knowledge of how the brain responds to auditory stimuli under different conditions, but also has potential to act as objective measures of speech intelligibility (Broderick et al, 2018;Di Liberto et al, 2018;Ding and Simon, 2012a;Lesenfants et al, 2019;Vanthornhout et al, 2018).…”
mentioning
confidence: 99%